The Living Experience as a design content: from concept to appropriation - Carolina Coelho (Ambiances)
This article aims to analyse the concept of the living experience applied to architecture, throughout the whole building’s lifecycle, from the design brief and spatial conception envisioned by the architect, to its materialization, and finally to the spatial appropriation undertaken by the user(s) - whether as individuals or as a group. Hence, it will start by focusing on the concept’s state of the art for separate authors and study fields, pointing out their approaches to architecture, and it will then refer to authors whom have applied this concept to the architectural design. Secondly, it will identify different design approaches and practitioners that value the living experience from the brief, either by using the most traditional and timeless architectural tools to the most recent ones. Finally, this article will focus on the way to identify and assess the living experience by the user(s), according to the different meanings mentioned above, the goals of the research and the features of each architectural space. Particularly, since each project enables a particular spatial fruition, it will explore a specific case study of an artistic school recently rehabilitated, which beholds a precise and multi-layered environment, potentiating both the learning process and the life within it.